1996
DOI: 10.1007/bf01193158
|View full text |Cite
|
Sign up to set email alerts
|

Untersuchung und Bewertung der Fumonisinkontamination von einheimischem und importiertem Getreide

Abstract: Cereal varieties cultivated in Germany, such as wheat, rye, grain-maize, barley, and oats were analyzed for fumonisins, including also imported maize from Argentina. In a total of 410 wheat samples and 140 rye samples of two harvesting years (1993, 1994) and in random samples of barley and oats no fumonisins were detected at all. In german grain-maize of 1993, only low fumonisin contents (17-33 ng/g) were detected occasionally. Some grainmaize samples of the 1994 harvest contained significantly higher fumonisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…For example, the results of a survey carried out in China indicated that fifty six per cent of samples (134/240) were found to contain fumonisin B 1 at levels ranging from 50-34868 μg/kg (Ueno et al 1997). Germany reported detection of fumonisins in 27% of samples (86/317) and levels ranged from 6-7132 μg/kg (Meister et al 1996). Continuous monitoring of these mycotoxins is required in order to assure that maize products containing high levels of fumonisins are not consumed by animals and humans.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the results of a survey carried out in China indicated that fifty six per cent of samples (134/240) were found to contain fumonisin B 1 at levels ranging from 50-34868 μg/kg (Ueno et al 1997). Germany reported detection of fumonisins in 27% of samples (86/317) and levels ranged from 6-7132 μg/kg (Meister et al 1996). Continuous monitoring of these mycotoxins is required in order to assure that maize products containing high levels of fumonisins are not consumed by animals and humans.…”
Section: Discussionmentioning
confidence: 99%